TECHNOLOGIES USING TELEPHONE APPLICATIONS IN EDO STATE, NIGERIA - Koyenikan, Margaret; Ohiomoba, I. S. (FUDMA Journal of Sciences, 2021)
The global crisis in Climate Change (CC) requires Climate Smart Agriculture (CSA) Information and Technologies (CSAITs) to address it. Mobile Phone Applications (MPAs) among other ICTs could be veritable tools for enhancing job performance of field staff by facilitating their generation and dissemination of relevant information to adapt, cope with and mitigate the effects of CC. This study examined access and dissemination of CSAITs using MPAs by field staff in Edo State Agricultural Development Programme (ADP). Specifically, it described the socio-economic characteristics, access and dissemination of CSA-related information, use of MPAs for CSAITs and the constraints to usage of MPAs among field workers. Data were collected from the 120 field staff comprising 78 Field Extension Workers and 42 Enumerators of Edo State Agricultural Development Programme (ADP), Nigeria. Data were analyzed using descriptive statistics and Pearsonâ€™s Product Moment Correlation (PPMC). Results show that 55.8% of respondents were males and 40.8% were between 41-50 years of age, 54.2% were HND/B.Sc holders and 50.8% had between 11-20years working experience. The CSAITs mostly accessed (â‰¥50%) using MPAs include irrigation and â€œfadamaâ€ farming, weather forecasts and zero or minimal tillage and non-burning while CSAITs mostly disseminated include manure application, mulching, and timely harvesting. The MPAs used for CSA-related tasks include voice calls ( =2.78), Short Messaging Service (SMS) ( =2.53), calculators ( =2.46), camera ( =2.46) and emails ( =2.43). Constraints to using MPAs for CSAITs-related tasks included inadequate knowledge and skills in CSAITs ( =3.72) and in the use of many MPAs and
Keywords: CSA Technologies, Telephone Applications usage, Field Workers, Nigeria